The Speed of Employer Learning - Lange, Fabian (Journal of Labor Economics, 2007)
The employer‐learning literature finds support for statistical discrimination on the basis of schooling. How economically relevant statistical discrimination is depends on how fast employers learn about workers’ productive types. This article is the first to estimate the speed of employer learning. Employers learn quickly. Initial expectation errors decline by 50% within 3 years. This estimate places an upper bound on the contribution of signaling. This bound varies with the speed of employer learning and with discount rate. For a wide range of parameter values, the contribution of signaling to the gains from schooling is less than 25%.